Regulation of Dopamine Uptake by Vasoactive Peptides in the Kidney - N. L. Rukavina Mikusic; N. M. Kouyoumdzian; E. Rouvier; M. M. Gironacci; J. E. Toblli; B. E. Fernández; M. R. Choi (Scientifica)
Considering the key role of renal dopamine in tubular sodium handling, we hypothesized that c-type natriuretic peptide (CNP) and Ang-(1-7) may regulate renal dopamine availability in tubular cells, contributing to Na+, K+-ATPase inhibition. Present results show that CNP did not affect either 3H-dopamine uptake in renal tissue or Na+, K+-ATPase activity; meanwhile, Ang-(1-7) was able to increase 3H-dopamine uptake and decreased Na+, K+-ATPase activity in renal cortex. Ang-(1-7) and dopamine together decreased further Na+, K+-ATPase activity showing an additive effect on the sodium pump. In addition, hydrocortisone reversed Ang-(1-7)-dopamine overinhibition on the enzyme, suggesting that this inhibition is closely related to Ang-(1-7) stimulation on renal dopamine uptake. Both anantin and cANP (4-23-amide) did not modify CNP effects on 3H-dopamine uptake by tubular cells. The Mas receptor antagonist, A-779, blocked the increase elicited by Ang-(1-7) on 3H-dopamine uptake. The stimulatory uptake induced by Ang-(1-7) was even more pronounced in the presence of losartan, suggesting an inhibitory effect of Ang-(1-7) on AT1 receptors on 3H-dopamine uptake. By increasing dopamine bioavailability in tubular cells, Ang-(1-7) enhances Na+, K+-ATPase activity inhibition, contributing to its natriuretic and diuretic effects.